A percepção das lideranças sobre as soft skills na indústria farmacêutica: a relação entre as habilidades sociais e o trabalho de equipes de vendas da indústria farmacêutica no Rio Grande do Sul - Niheues, Fabio Quadros (Universidade do Vale do Rio dos Sinos, 2022)
The present study aims to discuss an increasingly prevalent and current theme, inserted in our lives both personally and mainly professionally. It is the Soft Skills and their use, particularly by pharmaceutical industry sales leaders in Rio Grande do Sul. In a generous everyday life in possibilities, virtually rich in opportunities, characterized by the great wave of technologies, having professionals who achieve rapid adaptation and correct treatment of situations related to this context of transformation and people, is fundamental for the success of organizations. This environment in the pharmaceutical industry gains an even more challenging dynamic due to the base component in this business called innovation, which puts companies in a universe of competitiveness that is hardly seen in other sectors, needing constant selfassessment, especially in processes aimed at people. It is in this scenario, where technologies shorten distances and accelerate processes, marked by a lot of innovation and competitiveness, that we see the possibility and increasing need to have leadership focused on people management based on behavioral skills. For this reason, this research aims to understand how Soft Skills act in the business models of the pharmaceutical industry and its relationship with the leaders of this segment. In order to address the problem issue, qualitative research of exploratory and descriptive approach was carried out, through the method of field research study with bibliographic and documentary research, in the pharmaceutical industry, in the city of Porto Alegre, Rio Grande do Sul. During and after data collection, carried out through semistructured interviews, the data were analysed, which was carried out in responding to the specific objectives, identifying the understanding of the leadership theme and the challenges in the management of sales teams, the perceptions of leaders about Soft Skills and understanding the vision of these leaders in relation to the essential soft skills and the possible contribution to work with their sales teams.
Keywords: Soft skills; Liderança; Indústria farmacêutica; Líder; Leadership; Pharmaceutical industry; Leader; ACCNPQ::Ciências Sociais Aplicadas::Administração